A novel micro-mechanical model for prediction of multiaxial high cycle fatigue at small scales - Eslami, Reza (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
The grain microstructure and damage mechanisms at the grain level are the key factors that influence fatigue of metals at small scales. This is addressed in this work by establishing a new micro-mechanical model for prediction of multiaxial high cycle fatigue (HCF) at a length scale of 5-100?m. The HCF model considers elasto-plastic behavior of metals at the grain level and microstructural parameters, specifically the grain size and the grain orientation.